IbM KELOMPOK USAHA RUMAH TANGGA BORDIR DENGAN TEKNIK DESAIN BORDIR BERBASIS KOMPUTER - Murnomo, Agus; Setyowati, Erna; Andrasto, Tatyantoro (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2016)
In some sub-district in Semarang ubiquitous home household industry in the field of embroidery fabrics and the like, although quite large in number and spread out, but the existing potential has not been developed to the maximum. From field observations of potential home household scale industries in the field of embroidery in the area of Semarang has not been touched by technological advances design by utilizing IT (computer) and software applications to enrich the embroidery design. Based on surveys and direct interviews in several home industries in the field of embroidery are scattered in the region Semarang, that the problems faced can be grouped into three aspects, namely the facilities improvement of HR (human resources) that is knowledgeable about technology upgrading areas of the embroidery design, facilities and equipment, and management production in the field of embroidery where all three aspects are interrelated. This activity aims to answer the problems that exist, namely the training and tutorials embroidery design techniques with computer technology and its application. Improve the manufacturing facilities in the form of embroidery designs embroidery design software applications and the software application tool. Target outcomes that could result from this activity are: 1) Meyelenggarakan training and tutorials on the techniques of embroidery designs with computer technology, 2) Generate a variety of design styles of embroidery rocky computers, 3) pattern model of business management field of the embroidery professionally managed which can improve product in quality and quantity, 4) Improving synergies between universities and the business community in Semarang, 5) Resulting scientific articles in national journals in the context of publication of the results of activitie.